Are They the Greatest? A Visual Comparative Analysis of Muhammad Ali and Maya Angelou Published on American Newspaper Front Pages. Issue 3 (3rd July 2018) - Tait, Gabriel B.; Daniels, George L.
Abstract : This article explores the visual representation of the deaths of African Americans Muhammad Ali and Maya Angelou as presented on 150 front pages of America's newspapers. Considered by many as icons for their athletic, entertainment, and/or cultural contributions, Ali and Angelou were both represented in photographs, designs, and written content, which were analyzed in this study using visual semiotics theory as an interpretative framework. The analysis suggests that there are varying levels in the way icons are represented on these front pages. These representations often depend on the perceived societal contributions, type of vocation, and the visual significance of the cultural icon.